Hospital volume and mortality after transjugular intrahepatic portosystemic shunt creation in the United States. Issue 2 (27th December 2017) - Sarwar, Ammar; Zhou, Lujia; Novack, Victor; Tapper, Elliot B.; Curry, Michael; Malik, Raza; Ahmed, Muneeb
Abstract : The link between higher procedure volume and better outcomes for surgical procedures is well established. We aimed to determine whether procedure volume affected inpatient mortality in patients undergoing transjugular intrahepatic portosystemic shunt (TIPS). An epidemiological analysis of an all‐payer database recording hospitalizations during 2013 in the United States (Nationwide Readmissions Database) was performed. All patients ≥ 18 years old undergoing TIPS during a hospital admission (n = 5529) without concurrent or prior liver transplantation were selected. All‐cause inpatient mortality was assessed. Risk‐adjusted mortality was assessed for hospitals categorized into quintiles based on annual TIPS volume (very low, 1‐4/year; low, 5‐9/year; medium, 10‐19/year; high, 20‐29/year; and very high, ≥ 30/year). TIPS were placed in all 5529 patients (mean age, 57 years [standard deviation, ± 10.9 years]; women, n = 2071; men, n = 3458). Mortality decreased with rising annual TIPS volume (13% for very low to 6% for very high volume hospitals; P < 0.01). Elective admissions were more common in hospitals with higher annual TIPS volume (20.3% for very low to 30.8% for very high; P < 0.01). On multivariate analysis, compared with hospitals performing ≥30 TIPS per year, only hospitals performing 1‐4/year (adjusted odds ratio [aOR], 1.9; 95% confidence interval [CI], 1.21‐3.01; P = 0.01), 5‐9/year (aOR, 2.0; 95% CI, 1.25‐3.17; P < 0.01), and 10‐19/year (aOR, 1.9; 95% CI, 1.17‐3.00; P = 0.01) had higher inpatient mortality (20‐29/year: aOR, 1.4; 95% CI, 0.84‐2.84; P = 0.19). The absolute difference between risk‐adjusted mortality rate for very low volume and very high volume hospitals was 6.1% (13.9% versus 7.8%). TIPS volume of ≤ 20 TIPS/year, variceal bleeding, and nosocomial infections were independent risk factors for inpatient mortality in patients with both elective and emergent admissions. Conclusion : The risk of inpatient mortality is lower in hospitals performing ≥20 TIPS per year. Future research exploring preventable factors for higher mortality and benefits of patient transfer to higher volume centers is warranted. (Hepatology 2018;67:690‐699).